2019
DOI: 10.3389/fgene.2019.01111
|View full text |Cite
|
Sign up to set email alerts
|

Translated Long Non-Coding Ribonucleic Acid ZFAS1 Promotes Cancer Cell Migration by Elevating Reactive Oxygen Species Production in Hepatocellular Carcinoma

Abstract: Micropeptides (≤100 amino acids) are essential regulators of physiological and pathological processes, which can be encoded by small open reading frames (smORFs) derived from long non-coding RNAs (lncRNAs). Recently, lncRNA-encoded micropeptides have been shown to have essential roles in tumorigenesis. Since translated smORF identification remains technically challenging, little is known of their pathological functions in cancer. Therefore, we created classifiers to identify translated smORFs derived from lncR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Hepatocellular carcinoma (HCC), accounting for over 90% of all primary liver cancers, ranks the sixth most prevalent cancer in a world range. 1 The high HCC rates in parts of Asia majorly reflect the enhanced prevalence of chronic hepatitis B virus infection, with more than 8% of the population in this region chronically infected with the virus. 2 For all stages combined, liver cancer is among the cancer with the lowest survival rate (18%), highlighting the urgency to clarify novel mechanisms culminating in liver malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC), accounting for over 90% of all primary liver cancers, ranks the sixth most prevalent cancer in a world range. 1 The high HCC rates in parts of Asia majorly reflect the enhanced prevalence of chronic hepatitis B virus infection, with more than 8% of the population in this region chronically infected with the virus. 2 For all stages combined, liver cancer is among the cancer with the lowest survival rate (18%), highlighting the urgency to clarify novel mechanisms culminating in liver malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…While most would likely serve as negative controls as they would not be expected to encode gene products, other groups have shown that some lncRNAs may be translated into unstable peptides or even functional proteins, especially with the dysregulation induced by cancer. 40–42 Hence, we reasoned that a few might serve as antibody targets in patients with prostate cancer.…”
Section: Resultsmentioning
confidence: 99%
“…found that lncRNA ZFAS1 enhanced the proliferation of liver cancer by inhibiting miR-193a-3p ( 110 ). Recent research evidence has revealed that lncRNA ZFAS1 can encode a small peptide to down-regulate NADH dehydrogenase expression (NDUFA6, NDUFB11 and NDUFB4) to enhance ROS production, thus promoting cancer development ( 76 ).…”
Section: Lncrna Encoded Small Peptidesmentioning
confidence: 99%